2010
DOI: 10.1080/17438730903469805
|View full text |Cite
|
Sign up to set email alerts
|

The business of cultural heritage tourism: critical success factors

Abstract: This paper explores critical success factors (CSFs) required for cultural heritage tourism (CHT) operation and how these relate to commercial focus. The literature indicates tension between conservation of authenticity and commercial focus as it is seen to undermine authenticity, potentially degrading its quality and ultimate success as a tourism product. A list of nine key CHT business success factors was devised based on the published literature. Managers and operators of a range of Australian CHT operations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…concluded that barriers to participating in Indigenous tourism are related to age, gender, and origin (international or domestic). However, Hughes and Carlsen (2010) argue that enterprises with a strong financial planning, marketing, and market research appear to be successful even if authenticity is "met only partially" (Hughes & Carlsen, 2010, p. 31). However, Hughes and Carlsen (2010) argue that enterprises with a strong financial planning, marketing, and market research appear to be successful even if authenticity is "met only partially" (Hughes & Carlsen, 2010, p. 31).…”
Section: Visitors Interested In Participating In Indigenous Tourism Amentioning
confidence: 99%
“…concluded that barriers to participating in Indigenous tourism are related to age, gender, and origin (international or domestic). However, Hughes and Carlsen (2010) argue that enterprises with a strong financial planning, marketing, and market research appear to be successful even if authenticity is "met only partially" (Hughes & Carlsen, 2010, p. 31). However, Hughes and Carlsen (2010) argue that enterprises with a strong financial planning, marketing, and market research appear to be successful even if authenticity is "met only partially" (Hughes & Carlsen, 2010, p. 31).…”
Section: Visitors Interested In Participating In Indigenous Tourism Amentioning
confidence: 99%
“…Many researchers have found that finances, or an aspect of finances, are a vital CSF. The issue of finance may differ from one case to the next [accurate financial reporting (Brotherton et al 2003;Jaafar 2011), achieving accurate costing (Brotherton et al 2003), charging competitive prices (Brotherton & Shaw 1996), consideration of profit (Lucchetti & Font 2013), cost control (Geller 1985), cost of air travel (Ortigueira & GomezSelemeneva 2011), effective bad debt control procedures and effective revenue or yield management procedures (Brotherton et al 2003), financial performance (Avcikurt et al 2011), financial planning (Hughes & Carlsen 2010), financial support (Li, Wong & Luk 2006), payment models (Lin & Fu 2012), pricing (Brotherton 2004a)]. The results from this study differ in identifying different financial aspects such as not altering a quotation, absorbing costs and making a profit amidst an unstable currency.…”
Section: Theme 1: Financesmentioning
confidence: 99%
“…Thus, intrinsic conservation of cultural heritage capitalized in the hospitality sector affects environmental sustainability and investment decisions. Studies show that authenticity is a common factor of cultural heritage tourism places, regardless of commercialisation [31]. As concluded by Hughes and Carlsen, "conservation of cultural heritage authenticity and integrity is obviously important in terms of maintaining social and cultural value for the greater public good" [31, pp.…”
Section: Summary Results and Concluding Remarksmentioning
confidence: 99%